FOSTERING RELIGIOUS MODERATION: INTEGRATING VALUES INTO THE ENGLISH LANGUAGE TEACHING CLASSROOM - Dwi Nurrohmah, Indah; Puspitasari, Desi; Nadhifatul Mukaromah, Faizun (Kodifikasia, 2024)
Indonesia's diverse religious landscape, notably Islam, often grapples with extremism, contributing to socioeconomic disparities and a tarnished perception of faith. Such extremism poses a threat to national unity and the well-being of youths. In countering this trend, fostering religious moderation emerges as a pivotal strategy, discouraging the glorification of extreme doctrines. Education emerges as a crucial tool in instilling religious moderation values. This study investigates how religious moderation values integrate into English teaching settings. This study employed qualitative research. It involved three levels of Islamic institutions: Islamic elementary school (madrasa ibtidaiya), Islamic junior high school (madrasa tsanawiya), and Islamic senior high school (madrasa aliya) in Ponorogo. The researchers collected the data through in-depth interviews, observation, and documentation. The data, then, was evaluated thematically. This study revealed that religious moderation values were instilled into the lesson plans, learning materials, teaching-learning activities, and assessments in the English language teaching classroom.